2021
DOI: 10.1111/cas.14900
|View full text |Cite
|
Sign up to set email alerts
|

MZT2A promotes NSCLC viability and invasion by increasing Akt phosphorylation via the MOZART2 domain

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Recently, Wang et al reported that MZT2A mRNA and protein levels were overexpressed in NSCLC and associated with poor NSCLC prognosis. Upregulation of MZT2A could promote NSCLC cell viability and invasion by overexpressing LGALS3BP via the MTZ2A MOZART2 domain and Akt phosphorylation (34). However, mechanisms on how MZT2A influences tumor prognosis and CD8+ T-cell infiltration should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al reported that MZT2A mRNA and protein levels were overexpressed in NSCLC and associated with poor NSCLC prognosis. Upregulation of MZT2A could promote NSCLC cell viability and invasion by overexpressing LGALS3BP via the MTZ2A MOZART2 domain and Akt phosphorylation (34). However, mechanisms on how MZT2A influences tumor prognosis and CD8+ T-cell infiltration should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…MZT2A overexpression promoted NSCLC cell viability and invasion. Moreover, MZT2A indirectly induced Akt phosphorylation to promote NSCLC proliferation and invasion [ 116 ].…”
Section: Dysregulation Of the Other γ-Turc Building Componentsmentioning
confidence: 99%
“…The lack of MZT2A will weaken the nucleation activity of MT and slow down the rate of cell proliferation, and participate in the regulation of tumor cell cycle and cell proliferation. Wang H et al [ 15 ] found that high expression of MZT2A can promote the invasion of NSCLC tumor cells, and its overexpression level is associated with NSCLC progression and poor prognosis. However, there are few reports on the expression of MZT2A in different tumors and its relationship with disease prognosis and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the expression level of MZT2A in human cancers is critical for developing new therapeutic strategies. Wang H et al [ 15 ] found that MZT2A mRNA and MZT2A protein were highly expressed in non-small cell lung cancer ( NSCLC ). The expression of MZT2A protein in NSCLC cells was signi cantly higher than that in normal bronchial tissues, suggesting that MZT2A expression may promote the viability and invasion of NSCLC cells.…”
mentioning
confidence: 99%